Effects of fruit tissue pH value on the Penicillium expansum growth, patulin accumulation and distribution. Issue 12 (19th July 2022) - Wang, Min; Du, Yamin; Jiao, Wenxiao; Fu, Maorun
Abstract: pH is an important environmental factor for the virulence of fungi. To explore the effect of tissue pH on the diffusion behavior of Penicillium expansum and patulin, pear (pH 4.98), apple (pH 3.72) and kiwifruit (pH 3.31) were selected to inoculate P. expansum . When the diameter of the lesion was 1 cm or 2 cm, tissues within a certain distance (0, 1, 2, and 3 cm) from the lesion were sampled. Results showed that low pH could inhibit the growth of P. expansum and hinder patulin accumulation in the decayed parts. The quantity of P. expansum was 1.99 × 10 5 CFU/g and patulin content was 13.84 mg/kg in pear, which were 6.86 times and 92.89 times of that in kiwi‐fruit (lesion diameter 2 cm). In addition, the P. expansum colonies and patulin content decreased with the distance from the lesion, but there was no correlation between tissue pH and patulin distribution. Novelty impact statement: Low fruit tissue pH (pH < 4.98 ± 0.08) would inhibit the growth of Penicillium expansum and hinder the accumulation of patulin in the decayed parts. The pH value of the fruit tissue affects the diffusion behavior of P. expansum and patulin in different decayed fruits.